Shadow systems, risk, and shifting power relations in organizations - Furstenau, D.; Rothe, H.; Sandner, M. (Communications of the Association for Information Systems, 2017)
Drawing on notions of power and the social construction of risk, we build new theory to understand the persistence of shadow systems in organizations. From a single case study in a mid-sized savings bank, we derive two feedback cycles that concern shifting power relations between business units and central IT associated with shadow systems. A distant business-IT relationship and changing business needs can create repeated cost and time pressures that make business units draw on shadow systems. The perception of risk can trigger an opposing power shift back through the decommissioning and recentralization of shadow systems. However, empirical findings suggest that the weakening tendency of formal risk-management programs may not be sufficient to stop the shadow systems cycle spinning if they fail to address the underlying causes for the emergence of shadow systems. These findings highlight long-term dynamics associated with shadow systems and pose “risk” as a power-shifting construct.
Keywords: Business IT alignment; IT Governance; Power; Risk; Shadow systems